Examination of state-trait anxiety levels of elite athletes according to some variables - Burak Gurer; Haci Sahın; İlhan Adılogulları (Türk Spor ve Egzersiz Dergisi)
In this study it is aimed to examine state-trait anxiety points of elite athletes prior to and after competition in terms of several variables. 64 athletes, who competed in the branches of Judo, taekwondo and weightlifting of Turkish National Team during Mediterranean Games, attended this study. The data of the study is obtained by using the State-Trait Anxiety Inventory-STAI which is developed by Spielberger, Gorsuch, Lushene and later adapted by Oner and Le Compte. Scales are applied to athletes prior to and after the tournament. The state anxiety points of athletes after the competition are found to be significantly low compared to the points prior to the competition. This study demonstrates parallelism with our results. In conclusion, it would not be wrong to say that the ages of athletes affect trait anxiety level. When age variable is taken into consideration trait anxiety has become effective again. Thus, increasing age of elite athletes affects trait anxiety formation.